2007
DOI: 10.1016/j.molbiopara.2007.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a capping enzyme with specificity for the trypanosome spliced leader RNA

Abstract: Capping of the pre-mRNA 5' end by addition a monomethylated guanosine cap (m(7)G) is an essential and the earliest modification in the biogenesis of mRNA. The reaction is catalyzed by three enzymes: triphosphatase, guanylyltransferase, and (guanine N-7) methyltransferase. Whereas this modification occurs co-transcriptionally in most eukaryotic organisms, trypanosomatid protozoa mRNAs acquire the m(7)G cap by trans-splicing, which entails the transfer of the capped spliced leader (SL) from the SL RNA to the mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…Other proteins classified as essential (Alsford et al 2011) are found in the complexes, including the 117.5-kDa protein, which contains domains consistent with a role in RNA cap formation. Guanylyltransferase and N7-methyltransferase functions are required for the last two steps of eukaryotic mRNA cap formation (Ghosh and Lima 2010), however the enzyme identified here is distinct from that performing the nuclear co-transcriptional capping of the SL RNA, TbCGM1 (Ruan et al 2007;Takagi et al 2007; Sturm et al 2012). The further impact on distinct aspects of cell motility following knockdown of the TbE5 suggests unidentified roles for the complexes in the regulation of protein expression and function in these parasites.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Other proteins classified as essential (Alsford et al 2011) are found in the complexes, including the 117.5-kDa protein, which contains domains consistent with a role in RNA cap formation. Guanylyltransferase and N7-methyltransferase functions are required for the last two steps of eukaryotic mRNA cap formation (Ghosh and Lima 2010), however the enzyme identified here is distinct from that performing the nuclear co-transcriptional capping of the SL RNA, TbCGM1 (Ruan et al 2007;Takagi et al 2007; Sturm et al 2012). The further impact on distinct aspects of cell motility following knockdown of the TbE5 suggests unidentified roles for the complexes in the regulation of protein expression and function in these parasites.…”
Section: Discussionmentioning
confidence: 80%
“…The 47.5-kDa protein motifs are distinct, with the first containing a ferredoxin-like fold RNA-binding domain (97.7% confidence) and the second a yth domain RNA-binding motif (98.1% confidence) found in splicing factor yt521. The 117.5-kDa protein showed a superficial resemblance to the SL RNA cap 0 formation enzyme TbCGM1 (Ruan et al 2007;Takagi et al 2007) in the N7-methyltransferase domain (P-value = 0.54), as well as a bioinformatic kinship with the guanylyltransferase domain (P-value = 0.018) of a 142.1-kDa nucleoside triphosphate hydrolase/guanylyltransferase/zinc finger protein associated with the induction of stumpy bloodstream forms ( Fig. 7; Mony et al 2014).…”
Section: Knockdown Of the Tbeif4e5 Protein Affects Motilitymentioning
confidence: 99%
“…CBF5 silencing induces trans-splicing defects at the first step of splicing. Interestingly, the modification of cap 4 was perturbed in the CBF5-silenced cells (3), suggesting that SLA1 may function as a chaperone to maintain the proper secondary structure of SL RNA, essential for recognition by the methyltransferases (1,22,28,44) that mediate RNA cap 4 synthesis. SL RNA is transcribed by RNA polymerase II in a very special nuclear compartment near the nucleolus described for Trypanosoma cruzi (7).…”
mentioning
confidence: 99%
“…The high level of sequence similarity indicates that these genetic neighbors arose through a duplication event in the genome. TbCE1 is not thought to perform the cap 0 addition on the SL RNA, as that task is ascribed to the triphosphatase TbCET1 (15) and the bifunctional guanylyltransferase TbCGM1 (16,17).…”
Section: Immunolocalization Of the Tbe6mentioning
confidence: 99%
“…This trio of activities is found in various combinations in different systems, including three separate proteins in yeast, a pairing of the first and second activities in metazoa and plants or the second and third activities in kinetoplastids, and a single trifunctional enzyme in several viruses (14). In kinetoplastids the proteins adding cap 0 cotranscriptionally to the SL RNA are identified as TbCET1, a triphosphatase, and bifunctional TbCGM1, a guanylyltransferase and methyltransferase (15)(16)(17). Subsequent methylation of downstream nucleotides, referred to as cap 1, cap 2, and cap 4, can enhance translation levels (18).…”
mentioning
confidence: 99%